Social change and economic development in Nigeria - Damachi, Ukandi G.; Seibel, Hans Dieter (New York ; London : Praeger, 1973)
This book attempts to clarify the interplay of social change and economic development in Nigeria. The book has twelve contributors and is organized into four parts: the first is titled Social Aspects of Economic Development; the second, Manpower, Trade Unions, and Economic Development; the third attempts to highlight the role of education in the economic development process; and the last deals with Politics, Communications, and Economic Development.
Includes bibliographical references.
ne 24/04/2019
Loans
Keywords: Economic policy; Industrial relations; Social policy; Nigeria